Crisis-proof services: Why trade in services did not suffer during the 2008-2009 collapse - Andrea Ariu (National Bank of Belgium, 2015)
During the 2008-2009 crisis, trade in goods fell by almost 30%. In contrast, trade in business, telecommunication and financial services continued growing at their pre-crisis rates and only services related to transport declined. Using trade data at the firm-product-destination level for Belgium, I show that during the crisis the elasticity of services exports with respect to GDP growth in destination countries was significantly different from that of goods exports. In particular, the negative income shock in partner countries affected exports of goods but not exports of services. This difference is economically sizable: if goods exports had had the same elasticity to GDP growth as services exports, their fall during the 2008-2009 collapse would have been only half what was observed.
Keywords: F10; F14; L80; 330; Trade Collapse; Service Resilience; Trade in Services and Goods; Dienstleistungshandel; Wirtschaftskrise; Belgien